Human Influence on Desertification of Northeast Khorasan Province, Iran - Garivani, G M; Mokhanoy, E N; Shahandeh, H (Annals of Arid Zone, 2016)
Map of desertification process in the northern Khorasan region was compiled adopting methodology of FAO-UNEP and criteria devised by the Desert Institute of Turkmenistan for arid, and semi-arid regions. Based on Landsat-TM data, a desertification map of the region in 1972 was prepared and compared with human-induced desertification map compiled for northern Khorasan in 1999. -SoiL geologicaL topographic, climatic, agricultural, and sociological information were incorporated in compiling these maps. Data collected show that about 87% of the northern Khorasan region is affected by desertification, of which 55% is severely and very severely desertified. Around 6% of the area is not affected by desertification and 8% is a natural desert. The degradation of vegetation cover caused by human activities is the most extensive form of desertification, followed by water erosion, secondary salinization, and wind erosion. These cover 47%, 34%, 6%, and <1% of the area, respectively. Reversal of desertification in the early stages is essential in part of north-east Khorasan province before the region becomes severely desertified.